HUBUNGAN MASA KERJA DENGAN TINGKAT KOMPETENSI PROFESIONAL GURU DI SD NEGERI SE-KELURAHAN KISARAN KOTA - Zulaikha Halim Siregar; Masta Marselina Sembiring; Erlinda Simanungkalit (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to determine the relationship between tenure and the level of professional competence of teachers in public elementary schools throughout the Kisaran Kota sub-district. The population in this study were all public elementary schools throughout the Kisaran Kota sub-district, which amounted to 4 schools with a total of 60 teachers with a sample of 38 people. The data collection technique in this study used a questionnaire. While the data analysis technique used is quantitative descriptive analysis. Based on the results of the study, it can be concluded that the tenure of teachers in the Public Elementary Schools in Kisaran Kota is relatively high with an average of 25.42. The professional competence of teachers in public elementary schools in Kisaran Kota is high with an average of 99.74. In the normality test, it is known that the data is normally distributed because the 2-tailed significance value has a probability value of 0.951 > 0.05. In the linearity test of tenure (X) it is known that there is a linear relationship between tenure (X) and teacher professional competence (Y) because the significance value of deviation from linearity is 0.110 > 0.05. Keywords: Working Period, Competence, Professional, Teacher